EVALUATING STORE ATTRIBUTES OF TRANSMART CARREFOUR MANADO AS NEW STORE USING IMPORTANCE AND PERFORMANCE ANALYSIS - Amiman, Rene Joshua; Lapian, S.L.H.V Joyce; Tumewu, Ferdinand J. (Universitas Sam Ratulangi, 2018)
ABSTRACT: Shopping is an activity that people often do to fulfill their everyday needs. This becomes the main reason for business people to open a retail store. A retail store is a place that people visit to fulfill their wants and needs. Transmart Carrefour Manado is a newcomer in retail business in Manado. In Manado, Transmart must maintain their strategy in order to compete with other retail stores. This research aims to evaluate the importance and performance of store attributes in Transmart Carrefour Manado. Store attributes are important elements that are as important as marketing strategy. In order to determine the value of variables of store attributes, this research takes a quantitative approach using convenience sampling. This research uses Importance and Performance Analysis in order to analyze the data. Store Image, Product Availability, Discounts, Product Assortment and Retailers Attitude are the variables of Store Attributes. Based on the results of the analysis, Store Image, Retailers Attitude, Product Availability and Discounts have higher importance and performance values, and Product Assortment has lower importance and performance to consumers. Transmart Carrefour Manado has to maintain the high importance and performance of these variables.Keywords: store attributes, importance and performance analysis